2002
DOI: 10.1083/jcb.200105140
|View full text |Cite
|
Sign up to set email alerts
|

Fyn tyrosine kinase is a downstream mediator of Rho/PRK2 function in keratinocyte cell–cell adhesion

Abstract: The Rho GTPase and Fyn tyrosine kinase have been implicated previously in positive control of keratinocyte cell–cell adhesion. Here, we show that Rho and Fyn operate along the same signaling pathway. Endogenous Rho activity increases in differentiating keratinocytes and is required for both Fyn kinase activation and increased tyrosine phosphorylation of β- and γ-catenin, which is associated with the establishment of keratinocyte cell–cell adhesion. Conversely, expression of constitutive active Rho is sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
155
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(163 citation statements)
references
References 45 publications
7
155
0
Order By: Relevance
“…39,40,[44][45][46][47] Our study identifies CDK10/CycM as a key upstream regulator of this biology. Combining our and previous observations, we propose a model in which CDK10/ CycM phosphorylates PKN2 within its RhoA binding domain, thereby promoting RhoA binding and stabilization, which results in actin polymerization and consequent repression of primary cilia formation at cell cycle exit (Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…39,40,[44][45][46][47] Our study identifies CDK10/CycM as a key upstream regulator of this biology. Combining our and previous observations, we propose a model in which CDK10/ CycM phosphorylates PKN2 within its RhoA binding domain, thereby promoting RhoA binding and stabilization, which results in actin polymerization and consequent repression of primary cilia formation at cell cycle exit (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…This model is intriguing given the location of the CDK10/CycM phophosphorylation sites within PKN2, and the fact that cell-cell adhesion regulation depends upon the ability of PKN2 to bind RhoA, and vice versa. 44,45 If this model is correct, based on prior studies, 39 it must require active PKN2 kinase. In the second mechanism, CDK10/CycM-PKN2 could actively inhibit the Smurf1 complex.…”
Section: Discussionmentioning
confidence: 99%
“…For other cadherins, it has been reported that RhoA is stimulated by N-cadherin engagement in C2C12 myoblasts (Charrasse et al, 2002) and by E-cadherin engagement in keratinocytes (Calautti et al, 2002). However, other investigators have found that cell-cell contact through cadherins inhibits RhoA activity (Noren et al, 2001;Lampugnani et al, 2002), whereas still others detect no changes in RhoA upon cadherin engagement (Nakagawa et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Cell aggregation assays, which allow overall estimation of desmosome formation before they become calcium-insensitive, were performed essentially as described previously 51 Immunofluorescence staining of mouse skin. Frozen sections of mouse tail skin (7 mm) were incubated with antibodies against mouse Dsc2 (R&D Systems, Minneapolis, MN) or desmoplakin 52 together with Hoechst to counterstain nuclei.…”
Section: Methodsmentioning
confidence: 99%